Pengaruh Kecepatan, Temperatur dan Infill Terhadap Kualitas dan Kekasaran Kotak Relay Lampu Sign Sepedamotor Hasil dari 3D Printing - Joy H Panjaitan; Miduk Tampubolon; Fiktor Sihombing; Jamser Simanjuntak (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
3D printing technology has great potential in today's manufacturing world where one of its uses is in the prototype of a product. One of the most famous and inexpensive 3D printing technologies is the Fused Deposition Modeling (FDM) method. Many studies have been carried out using this FDM method. In this study, the printing of motorbike light relay boxes was carried out using the FDM method with two variations of speed, temperature and infill of each mass. 3D Printing uses a nozzle diameter of 0.4 mm and a work table temperature of 60oC and a height of 0.2 mm for each layer with support every where. From the research results, all the products produced have a rough surface with a level of geometric accuracy ranging from 0.91% for the length dimension and 7.73% for the width dimension of the product.